Identification and functional analysis of the LEAFY gene in longan flower induction - Dengwei Jue; Zhexin Li; Wenlin Zhang; Jianmin Tang; Ting Xie; Xuelian Sang; Qigao Guo (BMC Genomics, 2024)
Abstract Background Flowering at the right time is a very important factor affecting the stable annual yield of longan. However, a lack of knowledge of the regulatory mechanism and key genes of longan flowering restricts healthy development of the longan industry. Therefore, identifying relevant genes and analysing their regulatory mechanism are essential for scientific research and longan industry development. Results DlLFY (Dimocarpus longan LEAFY) contains a 1167 bp open reading frame and encodes 388 amino acids. The amino acid sequence has a typical LFY/FLO family domain. DlLFY was expressed in all tissues tested, except for the leaf, pericarp, and pulp, with the highest expression occurring in flower buds. Expression of DlLFY was significantly upregulated at the early flower induction stage in “SX” (“Shixia”). The results of subcellular localization and transactivation analysis showed that DlLFY is a typical transcription factor acting as a transcriptional activator. Moreover, overexpression of DlLFY in Arabidopsis promoted early flowering and restrained growth, resulting in reduced plant height and rosette leaf number and area in transgenic plants. DNA affinity purification sequencing (DAP-Seq) analysis showed that 13 flower-related genes corresponding to five homologous genes of Arabidopsis may have binding sites and be putative target genes. Among these five flower-related genes, only AtTFL1 (terminal flower 1) was strongly inhibited in transgenic lines. Conclusion Taken together, these results indicate that DlLFY plays a pivotal role in controlling longan flowering, possibly by interacting with TFL1.